The reality of the Algerian tax system and its impact on investment - Bassachi, Houda; sefha, Saliha (Journal of Research in Finance and Accounting, 2020)
The study aimed to introduce the reality of the Algerian tax system and its impact on investment, as the deterioration of economic conditions due to the oil crisis and the occurrence of equilibrium imbalances that were evident in the decline in GDP, employment and the decline in state revenues ... etc, reflected on the internal imbalance, as a result of the steady increase in expenditures Banking financing and planned investments, all of these reasons motivated the Algerian economy to witness reforms that affected a number of aspects, including the tax system, the aim of which was to increase tax effectiveness as a tool for financing, stimulate and direct investment, achieve justice and then achieve internal balances. The study found that laws exist in a form. Large, and are modified, canceled and renewed on an ongoing basis, which generated negative effects of the tax system.